Old Printed Books of the 18th Century in the Library Collection of the Ekaterinburg Theological Seminary - Andrey V. Poletaev (Вестник Екатеринбургской духовной семинарии)
The article provides materials on book archeography of the Cyril tradition. The work introduces readers to early printed books from the collection of the library in the Ekaterinburg Theological Seminary. It contains a scientific description of twelve old-printed books of the 18th century. Nine of the described codes were produced by the Synodal Printing House in Moscow: 1) Teaching Sunday Gospel (December, 1724); 2) Prologue for Summer (September, 1747); 3) Book of Hours (July, 1761); 4) John Chrysostom. Commentary on the Acts of the Holy Apostles. Andrew of Caesarea. Commentary on the Apocalypse. Vols. 1–2. 2nd ed. (March, 1768); 5) Cyril, Patriarch of Jerusalem. Teachings (April, 1772); 6) Ambrose, Bishop of Milan. About Positions (March, 1776); 7) John Chrysostom. Homilies on the Gospel of Matthew the Evangelist (November, 1781); 8) The Apostle (October, 1798); 9) Psalter with an Inscription (August, 1800). The Bible with “a newly corrected translation”, printed in September of 1762 and also known as the Elizabeth Bible (its first edition was issued on December 18, 1751, during the reign of Elizabeth Petrovna), was published by the Moscow Printing House. The book is presented in the description of the 4th edition. One book described in the article was produced by the Printing House of the Alexander Nevsky Monastery in St. Petersburg (August, 1724): it is a translated version of Wilhelm Stratemann’s work Featron, or Historical Shame. The description also includes a sample of an Old Believer publication — The Book, Called Psalter was issued by typographer F. K. Kartashev in Klintsovsky Posad, approx. 1794.